2005
DOI: 10.1177/0040517505054188
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Polyester Core-Spun Yarn with Spandex Using a Multi-section Drawing Frame and a Ring Spinning Frame

Abstract: Owing to growing demand for figure hugging and comfortable clothes made with stretchable fibers, spandex fibers are being used in underwear, diapers, hosiery, leisurewear, sportswear, jeans, and so on. In the present study a polyester core-spun yarn containing spandex fibers was made using a self-designed, multi-section drawing frame and a ring spinning frame. The mechanical properties of the core-spun elastic yarns were examined in various processing conditions. The analytical results show that when the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 6 publications
0
25
0
1
Order By: Relevance
“…A multi-section drawing frame and ring spinning frame were used to produce this yarn under various processing conditions and elastane draw ratio was optimized to improve the breaking tenacity and elongation of the yarn (Lou, Chang, Lin, Lei, & Hsing, 2005). A special positive feed drive mechanism and microcontroller system were developed to investigate the physical properties of elastane wool/ polyester yarn including tensile properties, hairiness, irregularity and fiber covering (Kakvan, Najar, Saidi, & Nami, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A multi-section drawing frame and ring spinning frame were used to produce this yarn under various processing conditions and elastane draw ratio was optimized to improve the breaking tenacity and elongation of the yarn (Lou, Chang, Lin, Lei, & Hsing, 2005). A special positive feed drive mechanism and microcontroller system were developed to investigate the physical properties of elastane wool/ polyester yarn including tensile properties, hairiness, irregularity and fiber covering (Kakvan, Najar, Saidi, & Nami, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Babay Dhouib, El Ghezal, and Cheikhrouhou (2004) concluded that the elastane draft and elastane ratio are important factors influencing the core spun yarn's mechanical properties. Furthermore, Lou, Chang, Lin, Lei, and Hsing (2005) determined the optimal draw ratio leading to higher breaking tenacity and elongation values. The elastic recovery is one of the most important properties that can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Core spun yarn can also be used as filling in which core part is Lycra filament and sheath fibres cotton, to improve the stretchability of denim [7,25,31,32]. The performance and comfort factors of these garments during use are very important.…”
Section: Introductionmentioning
confidence: 99%